Pengaruh Kualitas Pelayanan pada Loyalitas Pelanggan di Klinik Kecantikan MS Glow Yogyakarta: Kepuasan Pelanggan Sebagai Variabel Mediasi - Farhan, Fikri; Astuti, Vina Dwi; Hazmin, Gulam (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2025)
This research examines the influence of service quality on customer loyalty, mediated by customer satisfaction at Ms Glow Beauty Clinic in Yogyakarta. The study adopts a quantitative approach, utilizing primary data collected through a questionnaire. The sampling technique used was non-probability sampling, specifically purposive sampling, based on predetermined criteria set by the researchers. The sample criteria included Ms Glow Beauty Clinic customers aged 17-50 who had visited the clinic more than twice. A total of 200 respondents participated in the study. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS version 4.0.9.6. The research applied an outer model test to evaluate the validity and reliability of the measurement instruments and an inner model test to assess the relationships between variables. The findings reveal that service quality positively affects customer satisfaction, significantly enhancing customer loyalty. Furthermore, customer satisfaction mediates service quality and customer loyalty at Ms Glow Beauty Clinic in Yogyakarta.